The Risk of Arterial Thrombosis in Patients With Chronic Myeloid Leukemia Treated With Second and Third Generation BCR-ABL Tyrosine Kinase Inhibitors May Be Explained by Their Impact on Endothelial Cells: An In-Vitro Study - Haguet, Hélène; Bouvy, Céline; Delvigne, Anne-Sophie; Modaffari, Elise; Wannez, Adeline; Sonveaux, Pierre; Dogné, Jean-Michel; Douxfils, Jonathan (Frontiers in Pharmacology, 2020)
BCR-ABL tyrosine kinase inhibitors (TKIs) revolutionized the treatment of chronic myeloid leukemia, inducing deep molecular responses, largely improving patient survival and rendering treatment-free remission possible. However, three of the five BCR-ABL TKIs, dasatinib, nilotinib and ponatinib, increase the risk of developing arterial thrombosis. Prior investigations reported that nilotinib and ponatinib affect the endothelium, but the mechanisms by which they exert their toxic effects are still unclear. The impact of dasatinib and bosutinib on endothelial cells has been poorly investigated. Here, we aimed to provide an in vitro homogenous evaluation of the effects of BCR-ABL TKIs on the endothelium, with a special focus on the type of cell death to elucidate the mechanisms responsible for the potential cytotoxic effects of BCR-ABL TKIs nilotinib and ponatinib on endothelial cells. We tested the five BCR-ABL TKIs at three concentrations on human umbilical venous endothelial cells. This study highlights the endothelial toxicity of ponatinib and provides insights about the mechanisms by which it affects endothelial cell viability. In particular, ponatinib induced apoptosis and necrosis, whereas dasatinib affected endothelial cells by inhibiting their proliferation and decreasing wound closure. Comparatively, imatinib, nilotinib and bosutinib had little impact on endothelial cells at therapeutic concentrations, but inhibited proliferation. Overall, this study reports various effects of BCR-ABL TKIs on endothelial cells and suggests that ponatinib and dasatinib induce arterial thrombosis through endothelial dysfunction.